Study of the effectiveness of glucosamine and chondroitin sulfate, marine based fatty acid compounds (PCSO-524 and EAB-277), and carprofen for the treatment of dogs with hip osteoarthritis: A prospective, block-randomized, double-blinded, placebo-controlled clinical trial - Kampa, Naruepon; Kaenkangploo, Duangdaun; Jitpean, Supranee; Srithunyarat, Thanikul; Seesupa, Suvaluk; Hoisang, Somphong; Yongvanit, Karn; Kamlangchai, Phanthit; Tuchpramuk, Pongsatorn; Lascelles, B. Duncan X. (Frontiers in Veterinary Science, 2023)
Introduction Glucosamine hydrochloride and chondroitin sulfate are commonly used in dogs with OA, but evidence around efficacy is mixed. This study evaluated the effectiveness of glucosamine and chondroitin sulfate, marine based fatty acid compounds (PCSO-524 and EAB-277), and carprofen for the alleviation of canine hip OA pain. This was a prospective, block-randomized, double-blinded, placebo-controlled clinical trial. Methods Seventy-five owned pet dogs with hip OA were assigned randomly into five treatment groups: PCSO-524, Glucosamine and chondroitin sulfate, EAB-277, carprofen, and Placebo (sunflower oil). Peak vertical force (PVF) and subjective orthopedic assessment scores (OAS) were evaluated before treatment (week 0), and at weeks 2, 4, and 6 during treatment. Results At week 2, the carprofen group showed a significant increase in PVF (3.14 ± 5.33; mean ± SD). After 4 weeks, the increases in PVF of the PCSO-524 (3.90 ± 3.52), EAB-277 (4.17 ± 4.94), and carprofen (3.08 ± 5.87) groups were significant, and significantly greater than placebo (0.08 ± 1.90) and glucosamine (−0.05 ± 6.34) groups. After 6 weeks, the change of PVF in the PCSO-524 (4.14 ± 4.65), EAB-277 (4.45 ± 4.23), and carprofen (4.21 ± 6.52) groups were significant and significantly higher than the placebo group (−0.33 ± 3.65). The change in PVF in the glucosamine group (1.08 ± 5.49) lay between the placebo group and the other treatment groups. The OAS did not show any significant change in any group. Discussion PCSO-524 and EAB-277, but not glucosamine/chondroitin, resulted in significant improvements in PVF from baseline after 4 weeks, and 6 weeks, and to a similar degree to that seen with carprofen.